Between Two Revolutions: Cultural Relations between Mexico and Cuba - Kiddle, Amelia M. (Jahrbuch für Geschichte Lateinamerikas, 2017)
This article examines the role that Revolutionary Mexican foreign policy played within Mexican and Cuban society through an analysis of the 1938 voyage to Havana of the Brigada Mexicana and the 1939 visit to Mexico of Colonel Fulgencio Batista. These goodwill missions contributed to Mexican and Cuban state formation. In the Mexican case, the goodwill mission created domestic support by providing evidence of international support for the oil expropriation of 1938, and in the Cuban case, it provided legitimacy to the Batista regime by demonstrating affinity with the Mexican Revolution. While visiting Mexico in 1939, Batista witnessed the commemoration of the Constitution of 1917. Although he may not have been influenced to emulate its radical content in the Cuban Constitution of 1940, the two documents came to carry tremendous symbolic weight in the populist politics of both countries.